Intracellular Trafficking and Glycobiology of TbPDI2, a Stage-Specific Protein Disulfide Isomerase in Trypanosoma brucei - Schwartz, Kevin J. (American Society for Microbiology, 2013)
Trypanosoma brucei protein disulfide isomerase 2 (TbPDI2) is a bloodstream stage-specific lumenal endoplasmic reticulum (ER) glycoprotein. ER localization is dependent on the TbPDI2 C-terminal tetrapeptide (KQDL) and is mediated by TbERD2, an orthologue of the yeast ER retrieval receptor. Consistent with this function, TbERD2 localizes prominently to ER exit sites, and RNA interference (RNAi) knockdown results in specific secretion of a surrogate ER retention reporter, BiPN:KQDL. TbPDI2 is highly N-glycosylated and is reactive with tomato lectin, suggesting the presence of poly-N-acetyllactosamine modifications, which are common on lyso/endosomal proteins in trypanosomes but are inconsistent with ER localization. However, TbPDI2 is reactive with tomato lectin immediately following biosynthesis—far too rapidly for transport to the Golgi compartment, the site of poly-N-acetyllactosamine addition. TbPDI2 also fails to react with Erythrina cristagalli lectin, confirming the absence of terminal N-acetyllactosamine units. We propose that tomato lectin binds the Manβ1-4GlcNAcβ1-4GlcNAc trisaccharide core of paucimannose glycans on both newly synthesized and mature TbPDI2. Consistent with this proposal, α-mannosidase treatment renders oligomannose N-glycans on the T. brucei cathepsin L orthologue TbCatL reactive with tomato lectin. These findings resolve contradictory evidence on the location and glycobiology of TbPDI2 and provide a cautionary note on the use of tomato lectin as a poly-N-acetyllactosamine-specific reagent.